Prevalence of undiagnosed diabetes mellitus and associated factors among adult residents of Bahir Dar city, northwest Ethiopia: a community-based cross-sectional study - Getasew Mulat Bantie; Achenef Almaw Wondaye; Efrem Beru Arike; Mesfin Tenagne Melaku; Simegnew Tilaneh Ejigu; Abel Lule; Wondemagegn Mulu Lingerew; Koku Sisay Tamirat (BMJ Open)
Objective To assess the prevalence of undiagnosed diabetes mellitus (DM) and associated factors among adult inhabitants of Bahir Dar city, northwest Ethiopia.Design A community-based cross-sectional study was conducted on adults (n=607) of Bahir Dar city from 10 March to 20 May 2018.Measurements Data were collected using structured interviewer-administered questionnaire, and anthropometric measurements were taken from each participant. Fasting blood sugar (FBS) level was determined by samples taken early in the morning and readings of FBS≥126 mg/dL were classified as diabetes. The multivariate logistic regression model was fitted to identify the predictors of undiagnosed DM; adjusted OR (AOR) with a 95% CI was computed to assess the strength of associations.Result The study revealed that the prevalence of undiagnosed DM was 10.2% with 95% CI 7.9 to 12.9. Ever checked blood glucose level (AOR=1.91, 95% CI 1.03 to 3.51), don’t know the symptoms of diabetes (AOR=2.06, 95% CI 1.08 to 3.89), family history of DM (AOR=2.5, 95% CI 1.21 to 5.18) and body mass index (BMI) ≥25 kg/m2 (AOR=1.98, 95% CI 1.09 to 3.60) were factors associated with undiagnosed DM.Conclusion The magnitude of undiagnosed diabetes was high. Family history of DM, ever checked blood glucose level, don’t know about the symptoms of diabetes and overweight BMI were predictors of undiagnosed DM. Hence, screening and treatment are mandatory for high-risk groups. In addition, this study suggests frequent screening for those with family history and awareness creating about the disease for early detection and treatment.